2014
DOI: 10.4081/jphia.2014.334
|View full text |Cite
|
Sign up to set email alerts
|

Case based measles surveillance performance in 2010, littoral region of Cameroon

Abstract: The Littoral region of Cameroon met most of its routine immunization and surveillance objectives in 2010 but has not reiterated such a performance since then. We describe the case-based measles surveillance performance of 2010 by person, place, time and determine measles surveillance system delays. Descriptive statistics were performed using Epi Info 3.5.3. There were 130 suspected measles cases investigated by 17 (89.5%) health districts, 83 (64%) males and 99 (76%) ≤5 years. At least 4 cases were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…Most epidemiological analysis of measles surveillance data also showed that the status of more than half of cases was unvaccinated [ 17 21 ]. The proportion of vaccinated cases in this study was found to be higher (61.9%) than that of epidemiological analysis of measles surveillance data done in Cameron [ 13 ], Iran [ 22 ], Iraq [ 21 ] and Italy [ 18 ] that showed 49.2%, 20%, 18% and 5.5% of cases were vaccinated respectively. At the time of outbreak, it was concluded that outbreak was due to accumulation of susceptible population.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Most epidemiological analysis of measles surveillance data also showed that the status of more than half of cases was unvaccinated [ 17 21 ]. The proportion of vaccinated cases in this study was found to be higher (61.9%) than that of epidemiological analysis of measles surveillance data done in Cameron [ 13 ], Iran [ 22 ], Iraq [ 21 ] and Italy [ 18 ] that showed 49.2%, 20%, 18% and 5.5% of cases were vaccinated respectively. At the time of outbreak, it was concluded that outbreak was due to accumulation of susceptible population.…”
Section: Discussioncontrasting
confidence: 80%
“…In this study, median (delay time in days) interval between rash onset and case seen in health facilities seeking health care was 2.0 (IQR 1.0, 3.0). About two fifth cases, 846 (39.7%), visited health facilities within 48 h of onset of clinical sign and symptoms (Table 3 ) which was lower than that of Cameroon which reported 48.5% of cases visited within 48 h of onset of clinical sign and symptoms [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation